Adaptive coping strategies in patients with chronic pain conditions and their interpretation of disease - Büssing Arndt; Ostermann Thomas; Neugebauer Edmund AM; Heusser Peter (BMC, 2010)
Abstract Background We examined which adaptive coping strategies, referring to the concept of 'locus of disease control', were of relevance for patients with chronic pain conditions, and how they were interconnected with patients' life satisfaction and interpretation of disease. Methods In a multicenter cross-sectional anonymous survey with the AKU questionnaire, we enrolled 579 patients (mean age 54 ± 14 years) with various chronic pain conditions. Results Disease as an adverse interruption of life was the prevalent interpretation of chronic pain conditions. As a consequence, patients relied on external powerful sources to control their disease (i.e., Trust in Medical Help; Search for Information and Alternative Help), but also on internal powers and virtues (i.e., Conscious Way of Living; Positive Attitudes). In contrast, Trust in Divine Help as an external transcendent source and Reappraisal: Illness as Chance as an internal (cognitive) strategy were valued moderately. Regression analyses indicated that Positive Attitudes and higher age were significant predictors of patients' life satisfaction, but none of the other adaptive coping strategies. While the adaptive coping strategies were not associated with negative interpretations of disease, the cognitive reappraisal attitude was of significant relevance for positive interpretations such as value and challenge. Conclusions The experience of illness may enhance intensity and depth of life, and thus one may explain the association between internal adaptive coping strategies (particularly Reappraisal) and positive interpretations of disease. To restore a sense of self-control over pain (and thus congruence with the situation), and the conviction that one is not necessarily disabled by disease, is a major task in patient care. In the context of health services research, apart from effective pain management, a comprehensive approach is needed which enhances the psycho-spiritual well-being of patients.